Therapy with biphasic insulin aspart 30/70 (NovoMix 30) improves glycemic control in patients with type 2 diabetes mellitus: resultsfrom a Russian cohort of IMPROVE observational program designed to study safety and efficiency of biphasic insulin aspart 30 inroutine clinical practice - Marina Vladimirovna Shestakova (Endocrinology Research Centre, 2010)
Aim. To assess efficiency and safety of therapy at the onset and after intensification of the treatment with biphasic insulin aspart 30/70 (NovoMix 30)in patients with type 2 diabetes who failed to reach the desired level of glycemic control by using other forms of insulin. Materials and methods. The study included the Russian cohort of patients participating in the global IMPROVE program - a multi-center and multinationalopen observational non-randomized study for the evaluation of safety and efficiency of biphasic insulin aspart 30. Patients with type 2 diabetesmellitus were treated during 26 weeks under conditions of routine clinical practice. A total of 4869 patients enrolled in the program receivedantidiabetic treatment in the period preceding the study. 2430 of them were given oral hypoglycemic (OHG) agents alone and 2343 insulin +/- GHG.95 patients were preciously untreated. The dosage regime was prescribed by the attending physician on an individual basis. Most patients were poorlycompensated prior to the onset of the study. Their mean HbA1c level of 9.2% amounted to 9.9% in the untreated patients. Results of the treatment were analysed by the standard statistical methods for the entire cohort and for separate groups formed depending on previous therapeutic modality. Results. Six months after beginning of treatment with NovoMix 30, the HbA1c level significantly decreased by 2.34% in the entire cohort, 2.50% inthe previously untreated patients, and 2.13% in the two treated groups (p